Upaya Peralihan Negara Indonesia dalam Mengembangkan Energi Terbarukan - Fadya Dwi Kundaryanti; Pratiwi Ayu Retno Sari; Wahyu Kurniawati (CAHAYA: Journal of Research on Science Education, 2023)
In a country, energy plays an important role in everyday life. Energy is defined as the ability to do effort. All objects that can produce energy are called energy sources. The energy source itself is divided into two, namely non-renewable energy and renewable energy. Renewable energy is a source obtained from the earth's unlimited or inexhaustible natural resources such as wind, sun and others. In the utilisation of renewable energy sources, it has positive and negative impacts on the surrounding environment. It is not surprising that renewable energy sources have many positive impacts including reducing pollution by using environmentally friendly fuels or reducing greenhouse gas emissions, maintaining public health.